British Jewry and the Attempted Boycott of Nazi Germany, 1933–1939 (Theatrum historiae, 2017)
The article deals with the boycott of Nazi Germany, which the British Jews attempted in the years 1933–1939. The main question is why the Jewish boycott in Britain culminated in the summer of 1933 and why it was followed by years of stagnation. To what extent did the boycott movement have the chance to succeed is another key question as the main goal of the movement was nothing less significant than removing Hitler’s regime and thus preventing the war. The study is divided into three parts. The first part focuses on the initial phase of the boycott (1933–1934) and emphasises the fact that the main organisation representing British Jews, The Board of Deputies of British Jews, refused to make the boycott official. The second part points out gradual stagnation and the boycott’s downturn in the years 1935–1939. Although the Berlin Olympics in 1936 would have been a great incentive for the movement, they were not boycotted in the end. Then the movement was further weakened by the British policy of appeasement. The third phase of the study shows how the representatives of British Jewry attempted to influence the opinion of the government, especially the Foreign Office. Nevertheless, they failed in swinging political opinion towards the support of German Jews or the idea of a boycott. It became clear that the success of the boycott movement strongly depended on the official support; however, the mainstream political opinion preferred negotiations and agreement with Germany. The whole article is significantly based on yet unpublished sources from British and German archives.
Keywords: Jewish boycott; Nazi Germany; 1930’s; Jews in Britain; international relations